2016
DOI: 10.2298/tsci130327049a
|View full text |Cite
|
Sign up to set email alerts
|

MHD two-phase fluid flow and heat transfer with partial slip in an inclined channel

Abstract: The aim of this paper is to investigate the velocity and thermal slip effects in MHD flow and heat transfer of two-phase viscous fluid. It is assumed that both the phases have different densities, viscosities and electrical conductivities. The fully developed flow governed by a constant pressure gradient is passing through an inclined channel having inclination ϕ with horizontal axis. The electrical conductivity in phase I is assumed to be zero so that the constant applied magnetic field of strength B 0 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…In addition, Lorentz force could reduce the fow of fuids and it is a good means to control fuid fow. Similar results have been reported by Abbas et al [26] and Chamkha [7]. Te velocity in region I and II decreases from the interface to the boundaries of the regions and reaches its maximum velocity at the interface, as shown in Figure 2.Te couple stress parameter (s 1 � μ 1 h 2 /η 1 ) efect on the velocity components is shown in Figure 3.…”
Section: Efect Of Hartmann Number (Magnetic Parameter) and Couple Str...supporting
confidence: 87%
See 2 more Smart Citations
“…In addition, Lorentz force could reduce the fow of fuids and it is a good means to control fuid fow. Similar results have been reported by Abbas et al [26] and Chamkha [7]. Te velocity in region I and II decreases from the interface to the boundaries of the regions and reaches its maximum velocity at the interface, as shown in Figure 2.Te couple stress parameter (s 1 � μ 1 h 2 /η 1 ) efect on the velocity components is shown in Figure 3.…”
Section: Efect Of Hartmann Number (Magnetic Parameter) and Couple Str...supporting
confidence: 87%
“…Additionally, α ⟶ ∞, the slip coefcient (β ⟶ 0) represents the fow with no-slip boundary conditions. Similar to other researchers' fndings [26], it is also found that the velocity is increased in two phases by increasing the values of velocity slip parameters β 1 and β 2 (by decreasing α 1 and α 2 ).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Kumar et al [ 22 ] discussed the mixed convective flow and heat transfer in a vertical channel for the situation where only one of the phases is electrically conducting. Recently Abbas et al [ 23 ] investigated the velocity and thermal slip effects in MHD flow and heat transfer of two-phase viscous fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The velocity slip at the plate was introduced by Navier and named as Navier slip condition. The researchers [35][36][37][38] have used this condition due to its implementation in several industrial and engineering processes where the flow is confined by pipes, walls and curved surfaces. The mean velocity U can be computed by using the following relation…”
mentioning
confidence: 99%